Prevention of Falsification of Polygamous Marriage Identity in Lampung Province and Its Contribution to the Reform of Islamic Family Law in Indonesia - Billah, Yusuf Ridho (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article examines the problem of identity forgery in polygamous marriages in Lampung Province. This case arises because the husband is not open to the first wife and the strict regulations regarding polygamy. The purpose of the research is to analyse identity forgery from the perspective of Islamic law and positive law as well as preventive efforts that can be made as an Islamic family law reform in Indonesia. The method used is qualitative, with a case study approach, type of field research, data collection techniques, through observation, interviews and documentation. Interview respondents from the Head of the Lampung Province Religious Affairs Office, religious leaders and six perpetrators of marriage identity forgery. The findings show that identity forgery is done to trick the wife and the KUA, and violates the principles of justice in Islam and Marriage Law No. 1 of 1974. Prevention efforts involve increasing public awareness, the capacity of registration agencies, and revising stricter regulations. The conclusion states that these measures can prevent identity forgery and strengthen law enforcement, as well as contribute to a more just and transparent reform of Islamic family law.